EFFECT OF INBREEDING ON MORPHOLOGICAL TRAITS OF POPULATIONS OF GIANT FRESH WATER PRAWN, Macrobrachium rosenbergii: IMPLICATIONS FOR SELECTIVE BREEDING - Imron Imron; Harry Wuwungan; Dinar Tri Soelistyawati (Indonesian Aquaculture Journal, 2013)
Genetic improvement through selective breeding relies on the genetically-controlled phenotypic variability in the character of interest. Therefore, the extent of phenotypic variability in the population to be selected is an important parameter, as it potentially influences the population’s response to selection. This study was aimed to investigate the effect of inbreeding on the survivability, growth, and phenotypic variability of giant freshwater prawn (GFP), Macrobrachium rosenbergii. Two GFP populations of different inbreeding levels, namely 25% and 0%, respectively, were formed by mating of individual broodstock with known pedigree. Study was conducted for two months starting from newly hatched larvae up to nursery stage (30 day-old post larva). Phenotypic variability profile, expressed in the morphometric mean and coefficient of variation (CV) of twenty one morphometric characters were measured and evaluated. Results showed that in general, the inbred populations had lower values in the mean of all characters (100%), indicating that they suffered from inbreeding depression. Similarly, a lower CV values were observed in sixteen (75%) of the morphometric characters measured, indicating a potential reduced of genetic gain when they are used in selective breeding program. These results suggest the importance of controlling inbreeding level in breeding population that adverse effects resulted resulted from inbreeding can be minimized.